The Arts and Emergent Bilingual Youth : Building Culturally Responsive, Critical and Creative Education in School and Community Contexts. - Chappell, Sharon Verner (Taylor and Francis, 2013)
The Arts and Emergent Bilingual Youth offers a critical sociopolitical perspective on working with emerging bilingual youth at the intersection of the arts and language learning. Utilizing research from both arts and language education to explore the ways they work in tandem to contribute to emergent bilingual students' language and academic development, the book analyzes model arts projects to raise questions about "best practices" for and with marginalized bilingual young people, in terms of relevance to their languages, cultures, and communities as they envision better worlds.